2009
DOI: 10.1002/hed.21070
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of head and neck carcinomas by D‐allose

Abstract: Our results indicate that D-allose inhibits the growth of head and neck squamous cell carcinoma cells. D-allose has a considerable potential as a new anticancer agent in those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…In the pharmaceutical industry, for example, L-ribose can be used as a building block for drugs against cancers and viral infections. Its most important application is in antiviral Treatment of cancer, in particular chronic myeloid leukemia [3,34,72,76,116] Suppression of thrombus formation and reperfusion injury [4,35,77] Cryoprotectant for mammalian cells and organs [102] Immunosuppressant [36] D-Altrose Synthesis of cyclic carbamates of derived glycosylamines (polymer chemistry) [53,55] D-Arabinose Synthesis of antitumor compounds, such as dehydroamino acid derivatives [22,74,123] Production of D-erythroascorbic acid and oxalic acid [66] D-Gulose Drug-formulation agent and food additive [7] D-Idose Synthesis of cyclic carbamates of derived glycosylamines (polymer chemistry) [53,55] D-Lyxose Synthesis of antitumor and immunostimulatory agents [75,104] D-Psicose…”
Section: Introductionmentioning
confidence: 99%
“…In the pharmaceutical industry, for example, L-ribose can be used as a building block for drugs against cancers and viral infections. Its most important application is in antiviral Treatment of cancer, in particular chronic myeloid leukemia [3,34,72,76,116] Suppression of thrombus formation and reperfusion injury [4,35,77] Cryoprotectant for mammalian cells and organs [102] Immunosuppressant [36] D-Altrose Synthesis of cyclic carbamates of derived glycosylamines (polymer chemistry) [53,55] D-Arabinose Synthesis of antitumor compounds, such as dehydroamino acid derivatives [22,74,123] Production of D-erythroascorbic acid and oxalic acid [66] D-Gulose Drug-formulation agent and food additive [7] D-Idose Synthesis of cyclic carbamates of derived glycosylamines (polymer chemistry) [53,55] D-Lyxose Synthesis of antitumor and immunostimulatory agents [75,104] D-Psicose…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, we reported that d-allose inhibited the growth of head and neck cancer cells by inducing of cell cycle arrest, apoptosis and competition with glucose uptake (16). In addition, d-allose stimulates the overexpression of TRX-interacting protein (TXNIP) and enhances the effects of radiation (17).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing attention has been paid to this rare sugar due to its beneficial activities and potential pharmaceutical effects, such as antitumor [65], anticancer [66], anti-inflammatory [67], anti-oxidative [68], antihypertensive [69], cytoprotective [70], and immunosuppressant [71]. L-Rhamnose isomerase (EC 5.3.1.14), ribose-5-phosphate isomerase (EC 5.3.1.6), and galactose-6-phosphate isomerase (EC 5.3.1.26) were reported as potential enzymes for the bioconversion of D-psicose to D-allose [72].…”
Section: Reviewmentioning
confidence: 99%